The relationship between subcutaneous fat thickness and menstrual cycle on obese women - Eugene Talentino; Sutanto, Eviana Budiartanti; Safitri, Nathalia (World Nutrition Journal, 2025)
Background: Indonesian health survey shows an increase in obesity rates from 21.8% in 2018 to 23.4% in 2023. Obesity is a condition of excess fat accumulation that can be measured by the thickness of subcutaneous fat. Fat accumulation can disrupt the body’s hormonal condition because it also works as an endocrine organ. It produced aromatase that can disrupt the female reproductive hormonal system and causing menstrual disorders. 80% of women experience menstrual cycle disorders based on WHO in 2017. Objectives: To determine the relationship between the thickness of subcutaneous fat and menstrual cycle on obese women.